Theoretical framework for user-focused evaluation in office design - Minyoung Kwon (A+BE: Architecture and the Built Environment)
As was stated in the introduction, a user-focused renovation approach can enhance user satisfaction in offices and the functional quality of the offices while meeting energy performance goals. The first step for this renovation approach is to identify users’ needs and the physical and psychological factors affecting user satisfaction, as input to office renovation projects. The main aim is to identify the factors that are affecting the physical and psychological satisfaction of users, based on what previous research has found in that field. Therefore, this chapter highlights the main parameters currently applied to the evaluation of user satisfaction, including the definitions based on the literature review.